Isolation and genetic characterization of Acidovorax avenae from red stripe infected sugarcane in Northwestern Argentina - Fontana, Paola Daniela (2013)
Red stripe is a bacterial disease of sugarcane causing important economic losses in Argentina that affects 30 % of the milling stems and consequently the juice quality. In this study, sugarcane leaves exhibiting red stripe symptoms were sampled in the 2008–09 growing season from 13 different sugarcane producing areas of Tucumán and Salta (northwest of Argentina). To achieve the identification and characterization of the causal agent of red stripe, bacterial isolation was performed. Species-specific PCR using Oaf1/Oar1 primers allowed the amplification of a fragment of 550 bp from approximately 50 % of the isolates; 16S rDNA sequences analysis displayed a similarity greater than 99 % with Acidovorax avenae subsp. avenae. By means of RAPD-PCR the presence of at least four different biotypes among the analyzed isolates was detected. Results of pathogenicity test allowed us to confirm A. avenae subsp. avenae as the pathogenic agent for red stripe. This study constitutes the first report on the identification and molecular characterization of this plant pathogen from the Argentina sugarcane production areas. The genetic diversity observed among A. avenae is an important factor to be considered to improve an accurate diagnosis and/or the selection of sugarcane tolerant clones.